2020
DOI: 10.1155/2020/8843115
|View full text |Cite
|
Sign up to set email alerts
|

Heart Risk Failure Prediction Using a Novel Feature Selection Method for Feature Refinement and Neural Network for Classification

Abstract: Diagnosis of heart disease is a difficult job, and researchers have designed various intelligent diagnostic systems for improved heart disease diagnosis. However, low heart disease prediction accuracy is still a problem in these systems. For better heart risk prediction accuracy, we propose a feature selection method that uses a floating window with adaptive size for feature elimination (FWAFE). After the feature elimination, two kinds of classification frameworks are utilized, i.e., artificial neural network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Therefore, the construction of the Python course teaching model of computational thinking should be closely linked with the activity learning theory, and the teaching activities should be designed from the perspective of computational thinking so as to achieve the purpose of improving the comprehensive quality of students [ 28 ]. The same idea can be found in the diagnostic model proposed by Ashir Javeed et al [ 29 ], who have applied new methods to help doctors make accurate decisions in the diagnosis of heart disease.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the construction of the Python course teaching model of computational thinking should be closely linked with the activity learning theory, and the teaching activities should be designed from the perspective of computational thinking so as to achieve the purpose of improving the comprehensive quality of students [ 28 ]. The same idea can be found in the diagnostic model proposed by Ashir Javeed et al [ 29 ], who have applied new methods to help doctors make accurate decisions in the diagnosis of heart disease.…”
Section: Discussionmentioning
confidence: 91%
“…Cesarean section is an effective measure to rescue puerpera, fetal life and solve dystocia, and the risk of postoperative PPH is significantly higher than that of vaginal delivery [ 4 ]. At present, PPH patients are mainly treated by drugs and surgery, and for those whose hemostatic effect is not obvious, surgery is used for treatment [ 5 ]. As an effective and rapid treatment for PPH, hysterectomy is suitable for all kinds of PPH that have failed to be rescued.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 10 ML studies reported a total of 94,714 patients with heart failure. Of these, two prospective cohort studies [ 16 , 30 ] and one experimental study [ 11 ] used SVM for the prediction of heart failure, and two experimental studies [ 25 , 32 ] used ANN; two retrospective cohort studies [ 9 , 10 ] used LogR, and three studies [ 12 14 ] used GBM. The prediction of heart failure was associated with the result, which shows that GBM models achieved an average prediction accuracy of 91.10%, which is 4.40% higher than other models (e.g., ANN, SVM, and LogR).…”
Section: Results and Analysismentioning
confidence: 99%